Theoretical bases of planning of the system of advising on the professional career of students of professional educational establishments - Zakatnov, Dmytro (Professional Pedagogics, 2018)
Development of society radically changed from radical socio-economic and social and political transformations, what be going on in Ukraine. Market economy, labour-market, change in the system of education and other objective factors rendered considerable influence on preparation of young people to the choice of professional way. Thus forms and methods of the psychology and pedagogical providing of this process did not change substantially. The perspective variant of overcoming of contradiction between out-of-date forms and methods of the providing of process of preparation of studying young people to the choice and realization of professional trajectory and necessity of market of labour competitive, professionally mobile specialist’s saturation is creation of the system of advising for a professional career. The purpose of creation of the system of the quarry advising of student professional educational establishments is providing of choice student professional career on the basis of balancing of personality interests and necessities of labour-market in skilled competitive shots, and planning by them to the educational and professional trajectory.Advising for a career (career guidance) is the instrument of overcoming of personality conflicts of professional self-determination and professional development. His maintenance, forms and methods, must correspond the features of personality and professional development of man, what determines system requirement quarry advising on the stage of professional preparation taking into account its features in the system of trade education.
Keywords: professional career; quarry advising; system of the quarry advising for student establishments of trade education; quarry competence